Jack - Robinson, Marilynne (Farrar, Straus and Giroux, 2020)
"A new Gilead novel that tells the story of John Ames Boughton, the beloved, erratic, and grieved-over prodigal son of a Presbyterian minister from Gilead, Iowa"--